Nepetin inhibits osteoclastogenesis by inhibiting RANKL‐induced activation of NF‐κB and MAPK signalling pathway, and autophagy. Issue 24 (1st November 2020) - Chu, Binxiang; Chen, Shenao; Zheng, Xiaohe; Ye, Jiajing; Cheng, Xu; Zhang, Liwei; Guo, Di; Wang, Peng; Hong, Dun; Hong, Zhenghua
Abstract: Aseptic prosthetic loosening due to wear particle–induced inflammatory osteolysis is the main cause of failure for artificial joint replacement. The inflammatory response and the production of pro‐osteoclastic factors lead to elevation of osteoclast formation and excessive activity results in extensive bone destruction around the bone‐implant interface. Here we showed that Nepetin, a natural bioactive flavonoid with proven anti‐inflammatory and anti‐proliferative properties, potently inhibited RANKL‐induced osteoclast differentiation, formation and bone resorption in vitro, and protected mice against the deleterious effects of titanium particle–induced calvarial osteolysis in vivo. Mechanistically, Nepetin attenuated RANKL‐induced activation of NF‐κB and MAPK signalling pathways and TRAF6‐dependent ubiquitination of Beclin 1 which is necessary for the induction of autophagy. In brief, our study demonstrates the potential therapeutic application of Nepetin against osteoclast‐mediated osteolytic diseases.